Hermanson's case ; Olympics ; Hotdog [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Swedisn-German nationals caught by AFP suspected of helping the communist rebels in Quezon Province. A look at the allege anomalies in the Philippine delegation to Seoul Olympics. A look at the originators of the "Manila Sound" the first to bring Pinoy music to rock sound.